Manajemen Mutu Pendidikan: Kajian Sistematik tentang Implementasi dan Dampaknya terhadap Peningkatan Kualitas Sekolah di Indonesia - Diana Dwi Septyaningrum; Nur Faizah Zulfa; Hikmatul Hasanah; Mu’alimin Mu’alimin (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
Improving the quality of education is a strategic issue that is the main focus in the development of educational institutions in Indonesia. In the era of globalisation and digital transformation, educational institutions are faced with the demand to produce graduates who are not only academically excellent, but also adaptive to changes and community needs. One approach that has been widely studied to address these challenges is the application of educational quality management. This study aims to systematically review various studies that discuss the concept, implementation, and results of the application of educational quality management, with the main question being how the application of quality management contributes to improving the quality of educational institutions. This study uses a literature review method by searching for scientific articles from 2019 to 2025 accessed through Google Scholar and the Publish or Perish (PoP) application. The search was conducted using the keywords ‘educational quality management’, ‘quality implementation’, and ‘improvement of educational institution quality’. From the search results of 15 articles, five main articles were obtained and analysed in depth based on their relevance to the topic and contribution to the research focus. The results of the study revealed three main themes: first, quality management is implemented as a continuous improvement strategy that emphasises planning, implementation, evaluation, and follow-up on quality; second, transformational and collaborative leadership are determining factors in the successful implementation of quality management; third, the implementation of quality management has been proven to improve student academic achievement and the effectiveness of educational institutions. This study concludes that educational quality management plays a significant role in building a culture of quality, accountability, and professionalism among educators. Further research is recommended to explore models of digital and participatory quality management implementation in the context of 21st-century education.